PENGEMBANGAN KOLEKSI PERPUSTAKAAN KAJIAN TEORITIS ATAS KEBIJAKAN, PELUANG DAN TANTANGAN DI ERA INFORMASI - Yulinar Yulinar (Maktabatuna, 2019)
Collection Development is a number of activities related to the determination and coordination of selection policies, assessing user needs, collection usage studies, collection evaluations, collection needs, library material selection, collection maintenance planning and weeding collection of collection resources, and library collections. Principles of Collection Development consist of the objectives of collection development, collection development policies. Library collections are all library materials that are collected, processed, and stored to be presented to the public to meet the user's information needs. Library material procurement consists of determining the type of library material, selection of library materials, selection aids, procurement of library materials and finally doing weeding collections to remove collections from the shelves because they are not in demand, too many copies, there is a recent edition, and the collection is irrelevant. The decision was made based on consideration of the updating, suitability, and physical condition of the document.